The credit controller's desktop guide - Mason, Roger, 1944- (London : Thorogood, 2004)
The book includes valuable case studies and standard letters and forms.
Previous ed.: 1999.
uaj 05/05/2015
Loan
Keywords: Credit control -- Handbooks, manuals, etc